(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
In this essay I argue that we should consider Diogenes the Cynic’s claim to be cosmopolitan in light of his homelessness as a spatial and material reality. I do this order to arrive at a concept of cosmopolitanism that is more politically and ethically substantial than its typical rationalist Kantian formulations. I consider passages from Diogenes Laertius’ Lives of the Eminent Philosophers to clarify the relationship of homelessness to cosmopolitanism, and draw upon authors such as Emmanuel Levinas, María Lugones, and José Medina in order to demonstrate the fruitfulness of a reconsidered cosmopolitanism in our contemporary context. I ultimately suggest that Diogenes’ cosmopolitanism offers a rich and politically charged alternative to rationalist cosmopolitanism insofar as he points us towards critically rethinking both the cosmos and polis as expressions of political agency in a world in which homelessness and social exclusion are a common feature. I argue that cosmopolitan political practice would therefore be best understood fundamentally tentative, whether in the form of productive negotiation, or an interruptive displacement of hegemonic understandings of shared spaces.